The impact of EU immigration on economic growth through the skill composition channel - Șerban, Andreea Claudia; Aceleanu, Mirela Ionela; Dospinescu, Andrei Silviu; Țîrcă, Diana-Mihaela; Novo-Corti, Isabel (Technological and Economic Development of Economy, 2020)
The paper aims to examine the new trends of immigration and their implications on the economy of the host country, particularly on economic growth and unemployment. As the effects of aging population can be felt in many countries, especially in developed ones, migration will continue to play an increasing role in the economic growth of all countries, either sending or receiving. Given the changes in migration trends and migration policies, the impact of the process should be revised. One of the main characteristics that significantly impacts economic growth is the education and skill level of immigrants. In the light of this fact, the research aims to identify the impact of immigration on growth through the skill composition channel. We analyzed the impact of skilled and unskilled immigration on growth, also including the unemployment rate as a relevant factor for the labour market. We estimated six dynamic panel models using the system of generalised method of moments (GMM) to take into account the risk of an endogeneity bias of the migration variables. The results indicate a positive and significant effect of skilled immigration on the economic growth of the receiving country. The results also point to a 1.3 percent β-convergence rate consistent with the values found in the convergence literature which are around 2 percent.